Radiation dose and risk in children undergoing cardiac interventions performed using flat detector angiography systems. (15th November 2017) - Varghese, Anna; Devi, A; George, Paul V; Livingstone, Roshan S
Abstract: The purpose of the study was to measure radiation doses and estimate risk from various beam projections in children undergoing cardiac interventions. The dose area product (DAP) was measured for eleven patent ductus arteriosus device closures (PDA), four atrial septal defect device closures (ASD), and three balloon pulmonary valvuloplasty (BPV) interventions performed using a flat detector system. The total mean DAPs for PDA, ASD and BPV were 1.9 Gycm 2, 9.8 Gycm 2 and 6.2 Gycm 2 respectively. The fluoroscopic kerma dose rates increased by 10%, 33% and 92% when changing the projection from posterior–anterior to lateral projection for PDA interventions among infants, <5 yrs and >5 yrs respectively. The effective dose (ED) and organ doses were estimated from DAP using Monte Carlo software. Lungs received the highest organ dose of 7.4 mGy (PDA), 20.7 mGy (ASD) and 17.3 mGy (BPV) compared to other organs. The mean EDs from PDA, ASD and BPV were 2.5 mSv, 6.1 mSv and 4.9 mSv respectively. PDA intervention performed in infants had a radiation risk 66% higher than children aged between 3–10 years. Their lifetime attributable risk as per BEIR VII for cancer incidence was 1 in 907 males and 1 in 1047 females.